Purification Methods and the Presence of RNA in Virus Particles and Extracellular Vesicles - Yijun Zhou; Ryan P. McNamara; Dirk P. Dittmer (Viruses, 2020)
The fields of extracellular vesicles (EV) and virus infections are marred in a debate on whether a particular mRNA or non-coding RNA (i.e., miRNA) is packaged into a virus particle or copurifying EV and similarly, whether a particular mRNA or non-coding RNA is contained in meaningful numbers within an EV. Key in settling this debate, is whether the purification methods are adequate to separate virus particles, EV and contaminant soluble RNA and RNA:protein complexes. Differential centrifugation/ultracentrifugation and precipitating agents like polyethylene glycol are widely utilized for both EV and virus purifications. EV are known to co-sediment with virions and other particulates, such as defective interfering particles and protein aggregates. Here, we discuss how encased RNAs from a heterogeneous mixture of particles can be distinguished by different purification methods. This is particularly important for subsequent interpretation of whether the RNA associated phenotype is contributed solely by virus or EV particles or a mixture of both. We also discuss the discrepancy of miRNA abundance in EV from different input material.